PEMBIAYAAN PENDIDIKAN DASAR (SEKOLAH DASAR) DAN PERMASALAHNYA - Ananda, Rizki; Septira, Difva; Putri Nursida Aini; Rahmawati, Adinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Financing in basic education, particularly at the primary school level, represents a fundamental component of the national education system. It plays a critical role in enhancing the quality of educational services and promoting equitable access for all segments of the population. Despite the government’s efforts to provide various funding mechanisms-such as the Special Allocation Fund (DAK), the School Operational Assistance (BOS), and other financial resources-the implementation of education financing continues to encounter significant challenges. Key issues include disparities in fund distribution between regions, delays in budget disbursement, inadequate transparency and accountability in financial management, and limited managerial capacity at the school level. Additionally, the socio-economic conditions of local communities and the extent of local government involvement significantly influence the effectiveness of fund utilization. Therefore, a comprehensive evaluation of existing financing policies is essential, alongside efforts to strengthen the competencies of school administrators and improve monitoring and oversight systems. These strategic measures are necessary to ensure the realization of a basic education system that is equitable, inclusive, and of high quality on a sustainable basis.